The sexuales of Cinara palaestinensis Hille Ris Lambers, the Aleppo pine aphid (Hemiptera: Aphididae Lachninae) - Binazzi, Francesco; Pennacchio, Fabrizio; Peverieri, Giuseppino Sabbatini; Roversi, Pio Federico (Zootaxa, 2016)
The male and the oviparous female of Cinara palaestinensis Hille Ris Lambers, the Aleppo pine aphid, are recorded for the first time, in populations on Pinus halepensis in Italy. Description and illustrations are provided together with additional notes on taxonomy, ecology and distribution of the species.